2016
DOI: 10.1158/0008-5472.can-15-0536
|View full text |Cite
|
Sign up to set email alerts
|

H3K27 Demethylase JMJD3 Employs the NF-κB and BMP Signaling Pathways to Modulate the Tumor Microenvironment and Promote Melanoma Progression and Metastasis

Abstract: Histone methylation is a key epigenetic mark that regulates gene expression. Recently, aberrant histone methylation patterns caused by deregulated histone demethylases have been associated with carcinogenesis. However, the role of histone demethylases, particularly the histone H3 lysine 27 (H3K27) demethylase JMJD3, remains largely uncharacterized in melanoma. Here, we used human melanoma cell lines and a mouse xenograft model to demonstrate a requirement for JMJD3 in melanoma growth and metastasis. Notably, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…Therefore, the targeting of hyperplasia FLS highlights the therapeutic potential for RA. As one of the histone demethylases, JMJD3 is associated with tumor cell proliferation and metastasis in different types of cancer (28,29). In this study, we found that inhibition of JMJD3 strongly reduced cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, the targeting of hyperplasia FLS highlights the therapeutic potential for RA. As one of the histone demethylases, JMJD3 is associated with tumor cell proliferation and metastasis in different types of cancer (28,29). In this study, we found that inhibition of JMJD3 strongly reduced cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 48%
“…It ranks as the fifth most common cancer for male and the seventh most common malignancy in female (2,3). In recent years, a large number of studies have focused on the pathogenesis of MM, and deregulation of oncogenes and tumor suppressors have been reported to play key roles in the development and progression of MM (4,5). However, the detailed molecular mechanism underlying MM still remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The sphere-forming capability of various SCC cell lines in cell-cycle control, senescence, and differentiation, and may play a role in cancer development in a context-dependent manner (21)(22)(23). In fact, KDM6B expression is upregulated in several malignancies, such as Hodgkin's lymphoma (24), breast cancer (25), gliomas (26), melanoma (27), and renal cell carcinoma (28), while it is suppressed in others, including lung adenocarcinoma and squamous cell carcinoma (29), colon cancer (30,31), and liver and pancreatic cancers (32). While inactivating KDM6B gene mutations are only found in 1%-3% of SCCs (cBioPortal for Cancer Genomics; http:// www.cbioportal.org), the gene, like NOTCH1, has been implicated as a positive determinant of squamous cell differentiation (33).…”
Section: Introductionmentioning
confidence: 99%